Radio convergence: young people's radio listening habits in Cape Town - a comparative study - Ngomani, Noluyolo (Centre for Film and Media Studies, 2018)
The purpose of this study is to explore young people's radio listening habits in a time of radio convergence in South Africa. This study explores how the radio listening practices of youth studying and living in a township, for example Khayelitsha, differ from the practices of those who attend school in an urban area, for example Rondebosch, and acknowledging the University of Cape Town as a 'grey area' where diverse youth come together, by comparing Humanities and Science students. Drawing on Bourdieu's theories of capital, the study argues that various issues related to Internet access in South Africa, including communicative ecology, the historical background, and 'cultural capital' (Bourdieu, 1986; 1990), make the radio listening experience different for different groups, and strongly influence young people's radio listening habits. This argument is contextualized in relation to radio convergence which is seen through the use of social networking sites by radio stations, young people and people at large, and focusing especially on the growth of online-only radio with evidence of it being accessible to those that have access to the Internet. Furthermore, this study used both quantitative and qualitative methods to investigate the uses and gratifications as well as the social and individualistic act of radio listening, and the phenomenon of online-only radio. This study analyses the online radio stations Assembly Radio, CliffCentral and Ballz Visual Radio as case studies to show the dynamics of this medium, specifically highlighting programming, revenue, access to stations, and the reasoning behind their conception. In conclusion, the study argues that radio convergence should not be viewed as an erosion of the nature of traditional radio, but rather argues for convergence as an extension of the medium.